2012
DOI: 10.1371/journal.pone.0036886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standard Tuberculosis Treatment on Plasma Cytokine Levels in Patients with Active Pulmonary Tuberculosis

Abstract: BackgroundSputum Mycobacterium tuberculosis (Mtb) culture is commonly used to assess response to antibiotic treatment in individuals with pulmonary tuberculosis (TB). Such techniques are constrained by the slow growth rate of Mtb, and more sensitive methods to monitor Mtb clearance are needed. The goal of this study was to evaluate changes in plasma cytokines in patients undergoing treatment for TB as a means of identifying candidate host markers associated with microbiologic response to therapy.MethodsTwenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 45 publications
(52 reference statements)
8
65
3
Order By: Relevance
“…However, our findings did not reveal any significant differences in the expression levels of these factors in TB-infected children compared to those in control children. Since VEGF in particular has been shown to be a useful biomarker in adult TB (36,37), our findings suggest that more studies are needed on VEGF expression patterns before the utility of VEGF can be universally applied.…”
Section: Figmentioning
confidence: 93%
“…However, our findings did not reveal any significant differences in the expression levels of these factors in TB-infected children compared to those in control children. Since VEGF in particular has been shown to be a useful biomarker in adult TB (36,37), our findings suggest that more studies are needed on VEGF expression patterns before the utility of VEGF can be universally applied.…”
Section: Figmentioning
confidence: 93%
“…Multiple studies have demonstrated that there is a measurable and consistent response related to TB disease severity and or the effect of therapy [83][84][85][86][87][88]. Early evidence suggests that these responses will be informative before culture or microscopic conversion is currently detected [78,79,89,90].…”
Section: Potential Role Of Host-derived Biomarkers In Treatment Guidancementioning
confidence: 99%
“…[94] From these studies a number of promising markers have been selected, a notable example is IP-10/CXCL-10, a chemokine involved in the establishment of a proinflammatory Th1 response. TB is associated with increased serum IP-10 levels [93,[95][96][97], and at completion of therapy, levels are significantly lower than before treatment/at diagnosis. [64,98,99] This decrease is also measurable in the first weeks of therapy, [63,93] and therefore measurement of the kinetics of this cytokine during treatment may provide useful information on whether patients are responding to the prescribed drugs.…”
Section: Biomarkersmentioning
confidence: 99%